Sexual Violence Against Children from the Perspective of International Law - Maya Dyah Palupi; Rina Arum Prastyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The case of sexual violence against children from the perspective of international law highlights the importance of protecting children from all forms of sexual exploitation and sexual abuse. The purpose of this paper is to understand the forms of international law rules regarding cases of sexual violence against children and how international law prosecutes the perpetrators. The discussion of cases of sexual violence against children shows that these cases have serious and widespread impacts, with nearly 1.7 billion children worldwide experiencing violence. To address this issue, it is necessary to strengthen the legal framework that considers all behaviors related to Child Sexual Abuse and Male Sexual Abuse (CSAM) as criminal acts. Increasing resources in law enforcement, cooperation with the private sector, education, and relevant research are also important to increase our awareness of sexual violence. The conclusion that can be drawn is that children are indeed a new generation that will continue the continuity of nations and states, so it is only fair for us and law enforcement to ensure that all human rights of children are fulfilled.